Petroduric and 'petrosepiolitic' horizons in soils of Namaqualand, South Africa Horizontes petrodúricos y "petrosepiolíticos" en suelos de Namaqualand, Suráfrica Horizontes petrodúricos e petrosepiolíticos em solos de Namaqualand, África do Sul - Michele Louise Francis; Martin V. Fey; Freddie Ellis; Rosa María Poch (Spanish Journal of Soil Science)
Indurated, light-coloured 'sepiocrete' horizons have been found in Namaqualand Calcisols and Durisols. These horizons resembled calcrete but were non- to only mildly calcareous, resisted slaking in acid and alkali, and often broke with a conchoidal fracture. The presence of elevated quantities of sepiolite in the bulk-soil was confirmed by XRD analysis. The degree of induration in some these horizons suggested cementation by silica, and so in this paper the slaking properties, bulk chemistry, mineralogy and micromorphology of these horizons are compared with the typical silica-cemented, reddish-brown petroduric/duripan (dorbank) encountered in the region. 'Sepiocrete' horizons are chemically, mineralogically and morphologically distinct from the petrocalcic and petroduric horizons with which they are commonly associated. Micromorphology of the petroduric horizons revealed prominent illuviation in the form of oriented clay parallel to grains and crescent coatings on voids, a red matrix due to iron oxides, and translucent, isotropic amorphous silica coatings on grains and voids. In the 'sepiocrete' horizons, sepiolite appeared as a matrix of interlocking, sub-parallel fibres while the amorphous material was localised. The amorphous material was silica-rich with prominent aluminium and lesser magnesium; light brown under plane polarised light; not completely isotropic and had a lower birefringence than the sepiolite. The calcite was usually micritic, but also appeared as loose granules and as elongate crystals in a sepiolite matrix. The presence of the laminar Si-Al -rich areas on the sections suggested at the least localised duric properties and so mutual reinforcement of sepiolite and silica is possible. However, the 'sepiocrete' horizons did not meet the slaking requirements of the petroduric (dorbank) horizons and are distinct in appearance to the typical petroduric horizons in the region. They contained more MgO than the regions typical petroduric, and too little SiO2 to be silcrete. While the '-crete' terminology provides a useful expression of the cemented nature of the horizon, in order to fit existing soil classification and description schemes the terms 'sepiolitic' and 'petrosepiolitic' (in the same sense as 'calcic' and 'petrocalcic') are proposed and defined. The term 'sepiolitic' would be useful in the adjectival form in petrocalcic or petroduric horizons where sepiolite is significant but not the primary cement. The genesis of the 'petrosepiolitic' horizons is likely to be essentially similar to that of petrocalcic and petroduric horizons, except for chemical differences in the matrix solutions from which secondary minerals were precipitated, dictated by the pH and evaporative evolution of the soil solution. En Calcisols y Durisols de Namaqualand se encuentran horizontes endurecidos y de colores claros denominados sepiocretas. Estos horizontes son similares a calcretas pero no son calizos -o solo ligeramente-, resisten el colapso en ácidos y álcalis y tienen a menudo una fractura concoidal. Mediante análisis de difracción de RX se confirmó la presencia de elevadas cantidades de sepiolita. Debido a que la dureza de algunos de estos horizontes sugiere que están cementados por sílice, el objetivo de esta investigación es comparar su composición química, mineralógica y micromorfológica, así como su colapso, con las de los horizontes petrodúricos/duripanes (dorbank) pardo-rojizos cementados por sílice que se encuentran en la región. Los horizontes sepiocreta se distinguen de los horizontes petrocálcicos y petrodúricos con los que están comúnmente asociados desde los puntos de vista químico, mineralógico y morfológico. Los horizontes petrodúricos muestran una intensa iluviación en forma de arcilla orientada paralelamente a los granos y de revestimientos crecientes en huecos; una matriz rojiza debida a óxidos de hierro; y revestimientos isotrópicos amorfos translúcidos de sílice en granos y huecos. En los horizontes de sepiocreta la sepiolita se encuentra como una matriz de fibras entrelazadas subhorizontales, yuxtapuesta a un material amorfo compuesto principalmente de sílice, con considerables cantidades de aluminio y menos magnesio. Éste último es pardo claro en luz polarizada paralela, no completamente isotrópico y con una menor birrefringencia que la sepiolita. La calcita es normalmente micrítica, aunque aparece también como gránulos sueltos y cristales elongados en una matriz de sepiolita. La presencia de áreas con estructura laminar ricas en Si y Al sugiere que existen propiedades dúricas localizadas, por lo que no se puede descartar un refuerzo mutuo entre la sepiolita y la sílice. A pesar de ello, los horizontes de sepiocreta no cumplen los requisitos de colapso de los horizontes petrodúricos (dorbank) en la región, de los que difieren en aspecto. Contienen más MgO que los horizontes petrodúricos asociados, y no contienen suficiente SiO2 para ser clasificados como silcreta. Si bien la terminología -creta es útil para designar la naturaleza cementada de un horizonte, se proponen específicamente los términos sepiolítico y petrosepiolítico (análogos a cálcico y petrocálcico) para adaptarse a los sistemas de descripción y clasificación de suelos actuales. El término sepiolítico podría utilizarse como adjetivo en horizontes petrocálcicos o petrodúricos en que la sepiolita no es el principal agente cementante. Probablemente la génesis de los horizontes petrosepiolíticos es similar a la de los horizontes petrocálcicos y petrodúricos, excepto por las diferencias en la composición química de las soluciones matriz a partir de las que han precipitadosolución del suelo a medida que se evapora. Nos Calcisols e Durisols de Namaqualand encontram-se horizontes endurecidos e de cor clara denominados de se- piocretas. Estes horizontes são semelhantes às calcretas, porém, não são calcários (só ligeiramente), resistem ao colapso em ácidos e álcalis e freqüentemente têm fratura concoidal. Mediante análises de difração de RX confirmouse a presença de quantidades elevadas de sepiolita. Devido a que a dureza de alguns destes horizontes sugere que estão cimentados por sílica, o objetivo desta pesquisa é comparar a sua composição química, mineralógica e micromorfológica, assim como o seu colapso, com as de horizontes petrodúricos/duripans (dorbank) castanho-vermelhos cimentados por sílica que se acham na região. Os horizontes de sepiocreta distinguem-se dos horizontes petrocálcicos e petrodúricos com os que estão comumente associados do ponto de vista químico, mineralógico e micromorfológico. Os horizontes petrodúricos mostram intensa iluviação na forma de argila orientada paralelamente aos grãos e revestimentos crescentes em vazios; matriz vermelha devida aos óxidos de ferro; e revestimentos isotrópicos amorfos translúcidos de sílica nos grãos e vazios. Nos horizontes de sepiocreta a sepiolita se encontra como matriz de fibras interconectadas subhorizontais sobre material amorfo composto principalmente de sílica, com quantidades consideráveis de alumínio e menos magnésio. Este material é castanho claro em luz polarizada paralela, não completamente isotrópico e com menor birrefringência que a sepiolita. A calcita é normalmente micrítica, embora aparece também como grânulos soltos e cristais alongados em matriz de sepiolita. A presença de áreas com estrutura laminar ricas em Si e Al sugere a existência de propriedades dúricas localizadas, pelo que não pode-se descartar um esforço mutuo entre a sepiolita e a sílica. Apesar disso, os horizontes de sepiocreta não cumprem os requisitos de colapso dos horizontes petrodúricos (dorbank) na região, dos quais diferem também em aspecto. Contêm mais MgO que os horizontes petrodúricos associados e não contêm suficiente SiO2 para ser classificados como silcreta. Embora a terminologia -creta seja útil para designar a natureza cimentada de um horizonte, propõem-se especificamente os termos sepiolítico e petrosepiolítico (análogos a cálcico e petrocálcico) para adaptação aos sistemas de descrição e classificação de solos atuais. O termo sepiolítico poder-se-ia utilizar como adjetivo em horizontes petrocálcicos ou petrodúricos em que a sepiolita não seja o principal agente de cimentação. Provavelmente a gênese dos horizontes petrosepiolíticos seja similar à dos horizontes petrocálcicos e petrodúricos, exceto pelas diferenças em composição química das soluções matriz a partir das quais precipitaram os minerais secundários, regidos pelo pH e pela evolução da solução do solo na medida em que se evapora.